Assessment of true vertical root fracture line in endodontically treated teeth using a new subtraction software – A Micro‐CT and CBCT study. (14th December 2020) - Gulibire, Aihemaiti; Cao, Ya; Gao, Antian; Wang, Congyue; Wang, Tiemei; Xie, Xin; Liang, Jiahao; Li, Weifeng; Lin, Zitong
Abstract: This study aimed to find true facture lines in endodontically treated teeth on CBCT images using digital subtraction and to evaluate the influence of width of facture lines in the diagnosis. Thirty‐two endodontically treated teeth with vertical root fractures (VRFs) from 30 patients were included in this study. The CBCT images of the patients and the micro‐CT images of extracted teeth were imported into our digital subtraction software to distinguish the true facture lines from the streak artefacts. Of them, 23(71.87%) teeth did not present true fracture lines on the CBCT images (CBCT negative), and 9 (28.13%) teeth presented true fracture lines on the CBCT images (CBCT positive). The width of the facture lines was significantly different between these two groups ( P < 0.05). To summarise, for in vivo endodontically treated teeth with subtle VRFs, many true fractures lines could not be demonstrated on CBCT images and wider fractures could be better distinguished.